Environmental History and the Challenges of Interdisciplinarity: An Antipodean Perspective. (1st February 2003) - Pawson, Eric; Dovers, Stephen
Abstract : The environment has attracted more 'integrative' or 'interdisciplinary' efforts than any other substantive focus, one of which is the diverse and evolving field of environmental history. However, the theory and practice of interdisciplinarity, in environmental history and elsewhere, is unclear and contested ground. In this paper, we explore the nature of interdisciplinary work in environmental history. Drawing on three brief project narratives from environmental history, the paper discusses issues and problems, both intellectual and practical, that face those who seek to move across disciplinary boundaries in environmental history (as most of us do, wittingly or not). We then propose and discuss four 'intersections' that we believe have potential as loci of interdisciplinary engagement: mutual understanding; spatial scale and locale; time and change; and the environment and agency.